Volunteers as members of the stroke rehabilitation team: a qualitative case study. Issue 4 (9th April 2020) - Nelson, Michelle L A; Thombs, Rachel; Yi, Juliana
Abstract : Objectives: Clinicians are facing increasing demands on their time, exacerbated by fiscal constraints and increasing patient complexity. Volunteers are an essential part of the many healthcare systems, and are one resource to support improved patient experience and a mechanism through which to address unmet needs. Hospitals rely on volunteers for a variety of tasks and services, but there are varying perceptions about volunteers' place within the healthcare team. This study aimed to understand the role of volunteers in stroke rehabilitation, as well as the barriers to volunteer engagement. Design: A qualitative case study was conducted to understand the engagement of volunteers in stroke rehabilitation services within a complex rehabilitation and continuing care hospital in Ontario, Canada. Participants: 28 clinicians, 10 hospital administrators and 22 volunteers participated in concurrent focus groups and interviews. Organisational documents pertaining to volunteer management were retrieved and analysed. Results: While there was support for volunteer engagement, with a wide range of potential activities for volunteers, several barriers to volunteer engagement were identified. These barriers relate to paid workforce/unionisation, patient safety and confidentiality, volunteer attendance and lack of collaboration between clinical and volunteer resource departments. Conclusions: An interprofessional approach, specifically emphasising and addressing issues related to key role clarity, may mediate these barriers. Clarity regarding the role of volunteers in hospital settings could support workforce planning and administration.